2023
DOI: 10.1111/cas.15925
|View full text |Cite
|
Sign up to set email alerts
|

Clinico‐histological and molecular features of hepatocellular carcinoma from nonalcoholic fatty liver disease

Naoto Fujiwara,
Hayato Nakagawa

Abstract: Patients with nonalcoholic fatty liver disease (NAFLD) continue to increase with the epidemics of obesity, and NAFLD is estimated to become the most prevalent etiology of hepatocellular carcinoma (HCC). Recently, NAFLD‐HCC has been recognized to have clinico‐histologically and molecularly distinct features from those from other etiologies, including a lower incidence rate of HCC and less therapeutic efficacy to immune checkpoint inhibitors (ICIs). Consistent with the clinical observations that up to 50% of NAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…94 Therefore, accurate prediction of future HCC development from MASLD is crucial; however, it is still an unmet medical need. 95 We previously identified and validated a hepatic transcriptome-based 133-gene signature, named Prognostic Liver Signature for MASLD (PLS-MASLD), by analyzing human liver tissues in an unbiased manner. 35 To explore the biological aspects of PLS-MASLD, we performed a meta-analysis of human sc/snRNA-seq datasets with >100,000 cells encompassing almost all hepatic cell types, and subsequently integrated it with an spatial transcriptome data from human MASLD-affected liver using SPOTlight cell deconvolution algorithm.…”
Section: Chronic Liver Injurymentioning
confidence: 99%
“…94 Therefore, accurate prediction of future HCC development from MASLD is crucial; however, it is still an unmet medical need. 95 We previously identified and validated a hepatic transcriptome-based 133-gene signature, named Prognostic Liver Signature for MASLD (PLS-MASLD), by analyzing human liver tissues in an unbiased manner. 35 To explore the biological aspects of PLS-MASLD, we performed a meta-analysis of human sc/snRNA-seq datasets with >100,000 cells encompassing almost all hepatic cell types, and subsequently integrated it with an spatial transcriptome data from human MASLD-affected liver using SPOTlight cell deconvolution algorithm.…”
Section: Chronic Liver Injurymentioning
confidence: 99%
“…NAFLD can progress to nonalcoholic steatohepatitis (NASH) in 20-30% of cases, and approximately 20-25% of NASH cases progress to cirrhosis, which is the leading risk factor for HCC development [131][132][133][134]. During the past years, patients with NAFLD have continued to increase with the epidemics of obesity, with an estimate of one-third of the global adult population developing NAFLD, and NAFLD is estimated to become the most prevalent etiology of HCC [135,136]. It is reported that the addition of high cholesterol in high-fat diets can cause NASH in mice and augment carcinogenesis by increasing the multiplicity and size of tumors [106].…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Zhu et al performed integrated molecular analyses of HCC samples (n = from patients enrolled in the phase 1b or IMbrave150 phase 3 clinical trial of atezoliz and bevacizumab to identify potential biomarkers for predicting clinical outcomes existing immunity characterized by intratumoral CD8 T cell density, high expressi CD274 encoding PD-L1, and T-effector signature was favorably associated with the come, whereas a high regulatory T cell to effector T cell ratio and high expression o cofetal genes (GPC3 and AFP) were associated with reduced benefit from the combin therapy. A variety of underlying mechanisms that promote T cell accumulation w tumors have been revealed in animal models and comprehensive human HCC ana [23]. Ruiz de Galarreta et al showed that β-catenin activation promotes immune e by defecting dendritic cell recruitment and impairing T cell activity [24].…”
Section: Tumor Immune Microenvironment For Hcc and Ici Efficacymentioning
confidence: 99%